Sosialisasi Hukum Terkait Pencegahan Perilaku Menyimpang dalam Perspektif Hukum Islam - M. Bahtiar Ubaidillah; Sarbini Sarbini; Irwan Swandana; Derta Nur Anita; Ragil Ira Mayasari; Titik Khusumawati; Debrina Putri Buana; Kintan Puspita Wardani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Community Service Activities were carried out at Madrasah Aliyah Negeri (MAN) 1 Mojokerto with the target of understanding legal socialization related to preventing deviant behavior from an Islamic legal perspective. Implementation of community service The main aim of this activity is to increase insight and knowledge regarding the prevention of deviant behavior from an Islamic Law perspective at MAN 1 Mojokerto. In order to increase knowledge and insight regarding deviant behavior carried out by teenagers and how it is regulated in Islamic law. Therefore, the socialization carried out at MAN 1 Mojokerto, Mojosari District, Mojokerto Regency is very important to carry out. Where adolescence is a transition period from childhood to adulthood, where children are not yet fully able to be independent. At this time, teenagers are at the stage of searching for self-identity which is full of various problems. One of the problems experienced by teenagers in their lives is related to deviant behavior. Deviant behavior is chaotic behavior that causes a teenager to be nervous, nervous and act uncontrollably. This behavior is often a reflection of anti-social personality in teenagers, we can see this from behavior that does not heed religious and social norms. Trigger factors can come from the individual teenager himself (internal) or outside the teenager himself (external). As parents, educators (teachers) should naturally contribute to resolving deviant behavior in adolescents. Emotional development in adolescents has not yet reached stability, so to help solve the problem we must understand its characteristics.